2020
DOI: 10.1136/bmjopen-2019-034588
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the lived experiences of pregnancy and early motherhood in Italian women with congenital heart disease: an interpretative phenomenological analysis

Abstract: ObjectiveThis study explored the lived experiences of women with congenital heart disease (CHD) during pregnancy and early motherhood.DesignQualitative study using semistructured interviews. Data were analysed according to interpretative phenomenological analysis.SettingSan Donato Milanese, Italy.Participants12 adult women during pregnancy or early motherhood.ResultsThree main themes emerged from the analysis that were labelled as follows: ‘Being a woman with CHD’; ‘Being a mother with CHD’; and ‘Don’t be alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Resilience has been extensively researched concerning adjustment, positive psychological changes, and growth following adversity (Brémault-Phillips et al, 2020;Cheadle et al, 2020;Roepke & Seligman, 2014;Schaefer et al, 2019). Adaptation and positive changes are also reported in a study with pregnant women diagnosed with CHD and type 1 diabetes mellitus (Flocco et al, 2020;Sparud-Lundin & Berg, 2011). We also noted features of positive change and resilience in our study sample in Bosnia.…”
Section: Discussionsupporting
confidence: 81%
“…Resilience has been extensively researched concerning adjustment, positive psychological changes, and growth following adversity (Brémault-Phillips et al, 2020;Cheadle et al, 2020;Roepke & Seligman, 2014;Schaefer et al, 2019). Adaptation and positive changes are also reported in a study with pregnant women diagnosed with CHD and type 1 diabetes mellitus (Flocco et al, 2020;Sparud-Lundin & Berg, 2011). We also noted features of positive change and resilience in our study sample in Bosnia.…”
Section: Discussionsupporting
confidence: 81%
“…In this context, Nakamura et al revealed that some women might feel guilty in regard to possible risks for their own or their child's health or even for not being able to start a family with their partner. Flocco et al identified the fear of dying during pregnancy or birth as another burdensome factor for women with CHD (20). Even though women feel that having a child is part of a normal life and have a strong desire to become a mother, some women experienced the way towards pregnancy as highly burdensome.…”
Section: Mental Outcomes In Postpartum Women With Chdmentioning
confidence: 99%
“…They seem to look at pregnancy as one of the greatest battles of their life and therefore are proud and relieved to have won this fight (20). Furthermore, parenthood can lead to an increase in the sense of meaning and purpose (30).…”
Section: Mental Outcomes In Postpartum Women With Chdmentioning
confidence: 99%
“…The multidisciplinary nature of the research team, and the consequent integration of different perspectives and experiences, was also important during the analytic process ( Smith et al, 2009 ). In fact, the findings were constantly shared and discussed with the whole team, which enhanced the researchers’ reflexivity and thus reduced the influence of their preconceptions and biases on the analytic process, with increased rigor ( Smith et al, 2009 ; Larkin, 2018 ; Fiocco et al, 2020 ). Field notes were taken during and after each interview as an audit trail and were used to increase the quality of textual analysis.…”
Section: Methodsmentioning
confidence: 99%